(3ESgGeGJ GdeQGcR GdGSJcTGajI ddYdhe ai GdJchjf GdYdei dJdGejP eQMdI GdJYdje bHd GdLGeYi HeUQ (B: s (3OQGSI JJHYjI (B/ s - (3ShRGf SYjO SdjeGfs; (3EHQGgje GdOShbi YhV Gddg (B: s; (3fGOjI jhSa LeGd GdOjf (B: s ((3GdbGgQI (B: s (3ShRGf SYjO SdjeGf (B: s, 2020)
(3jgOa gPGGdHMK Edi JYQa eOjESgGe GdeQGcR GdGSJcTGajI ddYdhe ai GdJchjf GdYdei dJdGejP eQMdI GdJYdje bHd GdLGeYi HeUQ; h cja cGf Pdc GdESgGe? h GJHY GdHMK GdWQjbI GdfhYjI ai ELQGFg; h GSJNOe GdefgL GdJGQjNi h GdefgL GdGKfhLQGai; h GSJNOeJ GdebGHdI GdebffI h THg GdebffI cCOGI ddHMK; h TedJ YjfI GdHMK (B(10) (3CaQGO eef cGfhG jJQOOhf Ydi GdeQGcR GdGSJcTGajI ddYdhe CKfGA aJQI OQGSJge ai eQMdI GdJYdje bHd GdLGeYi HGdEVGaI Edi (B(3) (3ef ChdjGA CehQge(B: (3h (B(2) (3ef GdeTQajf GdYdejjf; h CLQjJ GdebGHdGJ aQOjI h Je LeY GdHjGfGJ h eYGdLGJgG(B: (3h GSJNdUJ GdfJGFLs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe CUhd GdJQHjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3ESgGeGJ GdeQGcR GdGSJcTGajI ddYdhes; (3GdJchjf GdYdeis; (3JdGejP GdJYdje bHd GdLGeYis